Some Further Developments in the Infinite Product Representation of Elementary Functions (Global Journal of Science Frontier Research, 2013)
An innovatory approach has been recently proposed for the derivation of infinite product representation of elementary functions. The approach is based on the comparison of different alternative forms of Green's functions for boundary-value problems stated for the twodimensional Laplace equation. A number of new infinite product representations of elementary functions was actually derived within the scope of that approach. The present study continues the trend: it aims at an analysis of the approach and exploring ways for its extending to some other problem statements that might also be efficiently treated.
Keywords: green’s functions; infinite products; elementary functions